To Analysis The Effect Of Scar Rehabilitation Along With Core Strengthening Exercises In Patient With Low Back Pain: A Randamozied Control Train - Puri, Ojha Akansha; Khan, Jafar; Warsi, Rahat khan; Sharma, Deepak; Pal, Renuka; Annamalai, KM.; Jain, Vardhman; Dubey, Sudhir; Joshi, Jayesh; Menaria, Dinesh (Journal of Neonatal Surgery, 2025)
Background;Low back pain (LBP) is a global musculoskeletal disorder with a high burden of chronic disability. Among post-cesarean women, abdominal scar tissue may play a significant but underrecognized role in persistent LBP due to fascial restriction and neuromuscular dysfunction. Aim;To analyze the effect of scar rehabilitation combined with core strengthening exercises on pain and functional disability in individuals with chronic low back pain. Materials and Methods;This observational study included 30 participants aged 21–60 years presenting with chronic LBP and abdominal scars (e.g., post-cesarean). Each underwent a structured protocol integrating scar mobilization and core strengthening exercises over several weeks. Pain and functional status were assessed pre- and post-intervention using the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). Statistical analysis was conducted using paired t-tests with significance set at p < 0.05. Results;A statistically and clinically significant improvement was observed following the intervention. The mean VAS score decreased from 5.79 ± 2.13 to 0.79 ± 0.77 (p < 0.001), and the mean ODI score decreased from 0.45 ± 0.16 to 0.04 ± 0.05 (p < 0.001). These improvements were consistent across gender, age groups, affected side, and pain duration. Conclusion;The findings support the hypothesis that abdominal scar tissue contributes to persistent LBP and that incorporating scar rehabilitation techniques into physiotherapy significantly reduces pain and disability. This integrative approach may be especially beneficial for post-surgical populations